Somatostatin receptors in congenital hyperinsulinism: Biology to bedside - van Albada, Mirjam E.; Mohnike, Klaus; Dunne, Mark J.; Banerjee, Indi; Betz, Stephen F. (Frontiers in Endocrinology, 2022)
Congenital hyperinsulinism (CHI), although a rare disease, is an important cause of severe hypoglycemia in early infancy and childhood, causing preventable morbidity and mortality. Prompt diagnosis and appropriate treatment is necessary to prevent hypoglycaemia mediated brain damage. At present, the medical treatment of CHI is limited to diazoxide as first line and synthetic somatostatin receptor ligands (SRLs) as second line options; therefore understanding somatostatin biology and treatment perspectives is important. Under healthy conditions, somatostatin secreted from pancreatic islet δ-cells reduces insulin release through somatostatin receptor induced cAMP-mediated downregulation and paracrine inhibition of β- cells. Several SRLs with extended duration of action are now commercially available and are being used off-label in CHI patients. Efficacy remains variable with the present generation of SRLs, with treatment effect often being compromised by loss of initial response and adverse effects such as bowel ischaemia and hepatobiliary dysfunction. In this review we have addressed the biology of the somatostatin system contexualised to CHI. We have discussed the clinical use, limitations, and complications of somatostatin agonists and new and emerging therapies for CHI.